An Approach for Attainment of Relevant Program Outcomes through Microcontroller Laboratory Course - Nayak, Aruna S.; Umadevi, F. M.; Preeti, T. (Journal of Engineering Education Transformations, 2017)
Embedded product design has emerged as an important area of study in the curriculum for undergraduate program in Computer Science. This necessitates the inclusion of hardware courses like Digital Electronics, Computer Organization and Microcontrollers as pre-requisite courses, in the lower semesters. This helps students to develop keen interest, skill and proficiency in the area of Embedded system design. This also helps them to compete with peers from other engineering branches in the domain of Embedded Systems. Here we present a set of activities, their related outcome based assessment techniques and outcome based strategies applied to the laboratory course on 8051 Microcontroller laboratory in Computer Science&Engineering at the IV Semester level. This laboratory was an extension of the hands on experience the students had in the course on Digital Electronics in the III Semester. The laboratory course on 8051 Microcontrollers was based on the usage of 8051 compatible Atmel 89C51ED2. The course was designed to consist of initially, conducting simple programming exercises using 8051 assembly language and then simple interfacing exercises using Embedded C programming. Later when they developed some proficiency and familiarity in 8051 environment student' teams were made to work on course projects which required them to design and build projects using 8051 or any other microcontroller of their choice. This promoted their self-learning, improved their knowledge of programming the microcontroller to interface with the outside world to develop useful applications and provide solutions to some common problems in society. This activity resulted in enhanced motivational levels amongst students, increased their involvement in the team and improved their knowledge due to self learning.